It is what it is [compact disc] - Thundercat; Childish Gambino, 1983-; Ty Dolla $ign, 1985- (Brainfeeder, 2020)
Produced by Flying Lotus and Thundercat, the album features musical contributions from Ty Dolla $ign, Childish Gambino, Lil B, Kamasi Washington, Steve Lacy, Steve Arrington, Badbadnotgood, Louis Cole, and Zack Fox.